2015
DOI: 10.1016/j.jhevol.2014.10.015
|View full text |Cite
|
Sign up to set email alerts
|

The use of museum specimens with high-throughput DNA sequencers

Abstract: Natural history collections have long been used by morphologists, anatomists, and taxonomists to probe the evolutionary process and describe biological diversity. These biological archives also offer great opportunities for genetic research in taxonomy, conservation, systematics, and population biology. They allow assays of past populations, including those of extinct species, giving context to present patterns of genetic variation and direct measures of evolutionary processes. Despite this potential, museum s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
192
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(205 citation statements)
references
References 109 publications
4
192
0
1
Order By: Relevance
“…Although complete mitochondrial genomes have been recovered from a number of museum specimens (10), such studies are still rare and mostly restricted to mammalian, or more infrequently bird, species. Our results show that DNA hybridization capture approaches can reliably be used to obtain DNA sequence data from museum specimens even in cases where traditional PCR-based approaches have failed because of poor DNA preservation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although complete mitochondrial genomes have been recovered from a number of museum specimens (10), such studies are still rare and mostly restricted to mammalian, or more infrequently bird, species. Our results show that DNA hybridization capture approaches can reliably be used to obtain DNA sequence data from museum specimens even in cases where traditional PCR-based approaches have failed because of poor DNA preservation.…”
Section: Discussionmentioning
confidence: 99%
“…DNA hybridization capture (7) is a powerful method that can be used to recover large amounts of sequence data while requiring very small amounts of input DNA. Although this approach has successfully been used to assemble complete mitochondrial genomes from highly degraded ancient DNA (8,9), only a few studies have so far reported full mitochondrial genomes being obtained from museum specimens, and to our knowledge, none of these investigated archival fish specimens (10). Fishes account for more than one-half of the diversity of the vertebrate tree of life and the relationships among many major groups remain unresolved or are based on morphological interpretations alone.…”
Section: Significancementioning
confidence: 99%
“…Natural history and medical collections in museums and universities around the world represent an enormous archive of biological and genetic information on diversity, taxonomy, and diseases (Austin and Melville 2006, Burrell et al 2015, Gilbert et al 2007). As pressure on wild populations has increased over the past 200 years, the rare and extinct species found in museums have become increasingly valued as samples for genetic studies and representations of biological history (Austin andMelville 2006, Burrell et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As pressure on wild populations has increased over the past 200 years, the rare and extinct species found in museums have become increasingly valued as samples for genetic studies and representations of biological history (Austin andMelville 2006, Burrell et al 2015). However, DNA extraction from archival specimens depends on their storage history, and it is widely known that formalin-preserved specimens give limited results for various reasons (Schander and Kenneth 2003, Austin and Melville 2006, Gilbert et al 2007, Dietrich et al 2013, Burrell et al 2015. Treatment with formalin-containing solutions results in crosslinks not only between proteins, but also between proteins and nucleic acids (Gilbert et al 2007, Dietrich et al 2013, Burrell et al 2015.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation